Octane upgrading by adsorption processes - Silva, José A.C. (2016)
In this work we studied the separation linear/mono/di-branched paraffins in a cyclic Pressure Swing Adsorption process using a layered bed of zeolites 5A and Beta (Figure 1). Zeolite Beta proved to be an efficient separator of mono-branched from di-branched paraffins. Aspen ADSIM (AspenTech Inc.) was used for numerically solve an adiabatic dynamic model incorporating mass, energy and momentum balances. Model parameters were taken from experimental data obtained in our lab. The studies were performed with the objective to determine how process performance is affected by purge quantity, 5A-to-Beta ratio,repressurization/blowdown schemes and operating temperature which are typical operating parameters of PSA processes.